Changing culture: learning into practice - Bert Lawrie (Scottish Journal of Residential Child Care)
The impact of unit culture on the life experiences of children in residential care is extremely important. This was recently recognised during the work of the National Residential Child Care Initiative (NRCCI) in Scotland.